Survey On PJOK Online Learning During the Covid-19 Pandemic at SMK Batik 1 Surakarta the Academic Year 2020/2021 - Ryo Sandy Ramadhan; Agus Kristiyanto; Tri Winati Rahayu (PHEDHERAL, 2022)
This study aimed to determine the implementation of online sports learning at Vacation High School Batik 1 Surakarta The 2020/2021 academic year. This study used a quantitative descriptive method with a one shot case study approach with one time data collection. The subjects in this study were Class XI students of Vacation High School Batik 1 Surakarta, totaling 66 students. The researcher used two types of data, namely primary and secondary data, for data collection techniques used questionnaires and documentation. The data obtained from the questionnaire results were analyzed and tested for validity using SPSS program version 25 for windows.The results of the research could be explained that the implementation of online sports learning at Vacation High School Batik 1 Surakarta is carried out well by students, namely students on average agree with percentage of 60% based on the planning dimension, 61% agree based on the implementation and learning process dimensions, and 62% agree based on the dimensions evaluation of learning outcomes.This study concluded that the average percentage of students agreeing in Sport Online Learning at Vacation High Schools Batik 1 Surakarta has been said to have been carried out well. It is expected that this research can be useful input for sports teachers in online sports learning and can be used as knowledge and application for PJOK teachers as a study of the development of sports science in the future.